PENGGUNAAN ARANG AKTIF KULIT KACANG TANAH (Arachis hypogaea) SEBAGAI ADSORBEN DALAM PRODUKSI KAROTEN DARI FRAKSI OLEIN MINYAK SAWIT KASAR - Nurhaeni Nurhaeni; Ni Ketut Sumarni; Eka Dwiyanti Tombilayuk (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
Research using active charcoal leather peanut (Arachis hypogaea) as adsorbent in carotene production of crude palm oil olein fraction has conducted. This study aims to determine the ratio between active charcoal and olein that can produce the highest carotene shake time for 3 hours. Carotene analysis was conducted using UV-Vis spectrophotometry. The study design is applied is completely randomized design (CRD), with 5 variations adsorbent ratio is 1: 5; 1,5: 5; 2: 5; 2,5: 5; 3: 5 w/v and each stage is repeated twice. Results of this research showed that the ratio of peanut skin adsorbent 2: 5 w/v have the best adsorption weighing carotene obtained at 0,72 mg and percent absorption by the adsorbent reaches 97,3%.Keywords: Peanut Leather, Adsorbents, UV-Vis spectrophotometry, Carotene.